Altered frontotemporal glucose metabolism following radiotherapy and/or chemotherapy for cervical cancer - Hu, Yao; Zhong, Yuan; Hu, Yuxiao (Frontiers in Neurology, 2025)
BackgroundLittle is known about the effects of subphrenic radiotherapy on brain glucose metabolism in patients with cervical cancer (CC) after chemotherapy. This study aimed to explore the effects of radiotherapy, chemotherapy, and radiochemotherapy on brain glucose metabolism in patients with CC.MethodsA total of 237 CC patients who underwent 18F-fluorodeoxyglucose (18F-FDG) positron-emission tomography (PET)/computed tomography (CT) were included, consisting of 88 patients without treatment, 61 patients with radiotherapy, 24 patients with chemotherapy and 64 patients with radiochemotherapy. One-way analysis of variance (ANOVA) was used to explore the effects of chemotherapy, radiotherapy and radiochemotherapy factors on brain PET data in CC patients by using statistical parametric mapping (SPM).ResultsCompared to CC patients without treatment, hypometabolism in some frontal and temporal lobes and no hypermetabolic regions were observed in those with radiotherapy (PFWEc < 0.05), while no significant brain metabolic areas was found in those with chemotherapy. Some above hypometabolic regions identified in radiotherapy and some other hypometabolic regions were found in patients with radiochemotherapy relative to those without treatment (PFWEc < 0.05). In addition, comparing any two of the radiotherapy, chemotherapy and radiochemotherapy groups only found significantly altered brain metabolic regions located in the right lingual gyrus between the radiotherapy and chemotherapy groups (PFWEc < 0.05).ConclusionRadiotherapy might decrease metabolism in the temporal and frontal lobes in CC patients. Furthermore, chemotherapy and radiotherapy might synergistically decrease glucose metabolism in some frontotemporal regions of CC patients, which might indicate potential cognitive impairment and emotional disorders.